A microbial assessment of instrumentation and noninstrumentation laser disinfection technique: An in vivo study - Anaida Clara Alex; I. B. Geeta; R. Vinay Chandra; B. Arvind (Wolters Kluwer Medknow Publications, 2024)
Aim: The present study aimed to compare the reduction in microbial count of instrumentation versus noninstrumentation laser disinfection technique. Methods: Thirty patients with periapical lesions ranging 3-5 mm in single-rooted teeth were selected for the study. The groups were divided into two main groups: Group 1 - instrumentation technique and Group 2 - noninstrumentation technique subjected to laser disinfection. Group 2 was again subdivided into two groups: Group 2A - only laser disinfection and Group 2B - laser disinfection and medicament. The groups were analyzed for the reduction in microbial count. The Kruskal-Wallis test was used to compare mean differences in colony-forming unit (CFU) counts. Post operative mean CFU between the three groups were compared using Dunn's Post Hoc analysis. The level of significance was set at P < 0.05. Results: Significant differences were noted in mean CFU counts between Group 1 and Groups 2A and 2B (P = 0.006 and P = 0.001, respectively). Among Groups 2A and 2B, the reduction in the microbial count of Group 2B is better than 2A although not significant. Conclusion: Significant shifts were observed in both the groups, but the impact of the shift was greater in the laser-assisted groups. Noninstrumentation laser disinfection technique shows promising results when compared to conventional techniques.